Analisis Budaya Belajar Matematika Siswa di SMA Muhammadiyah Pondok Pesantren Imam Syuhodo - Hidayati, Indriyana Nur; , Dr. Sumardi, M.Si (2017)
This study aims to describe the learning culture of students mathematics in school and students learning culture in the dormitory. This type of research is qualitative ethnography. The subjects of this study are students of class XI IPA and XI IPS 2 SMA Muhammadiyah Pondok Pesantren Imam Syuhodo. Data collection techniques use observation, interviews, and documentation. The validity of data is done by triangulation method by comparing data of result of observation method, interview, and documentation. Data analysis techniques performed with data reduction, data presentation, and conclusion. The results of this study found that there are two kinds of cultural learning bealajar both at school and in the dorm. The learning culture is a culture ofelf-learning and group learning culture. Culture of mathematics learning in groups more selected by students both at school and in the dorm. The interaction that exists between teacher and student while learning mathematics in the classroom is fun, it is marked by students' enthusiasm during the learning of mathematics in the classroom. The method often applied in the classroom is the lecture method.